Bone Health Improvement Protocol - Wool, Nathan K.; Wilson, Shannon; Chong, Alexander C.M.; Dart, Bradley R. (Kansas Journal of Medicine, 2017)
Introduction. Metabolic bone disease is a malady that causessignificant morbidity and mortality to a patient who has sustaineda fragility fracture. There is currently no protocol toprevent secondary fragility fracture at our institution. The objectiveof this study was to create an appropriate protocol forimplementing clinical pathways for physicians to diagnose andtreat osteoporosis and fragility fractures by educating patients.Methods. A multidisciplinary team created an appropriateprotocol that could be implemented in an inpatient setting.A thorough literature review was conducted to evaluatepotential barriers and efficacious methods of protocol design.Results. A bone health improvement protocol was developed.Any patient over the age of 50 who sustains a fracture from lowenergy trauma, such as a fall from standing or less, should beconsidered to place into this protocol. These patients receivededucation on metabolic bone disease, a prescription for highdose vitamin D therapy, and laboratory testing to determinethe etiology of their metabolic bone disease. Continuity of careof these patients with their primary care provider was providedfor further management of their metabolic bone disease andevaluation of their disease after discharged from the hospital.Conclusion. Comprehensive secondary prevention should consistof osteoporosis assessment and treatment together with afall risk assessment. With this protocol, secondary fragility fracturespotentially could be prevented. KS J Med 2017;10(3):62-66.